2011
DOI: 10.3109/07853890.2011.588246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate red wine consumption on liver fat and blood lipids: a prospective randomized study

Abstract: Methods: Thirty-two healthy women and 12 healthy men (34±9 years of age) were randomized to consume 150 ml of red wine/day for women (16g ethanol/d) or the double amount for men (33g ethanol/d), or to alcohol abstention during 90 days.Participants underwent proton-nuclear magnetic-resonance spectroscopy for measurement of hepatic triglyceride content (HTGC). Blood samples for assessment of cardiovascular risk were drawn before and after the intervention.Results: After exclusion of three subjects with steatosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
(42 reference statements)
4
35
2
2
Order By: Relevance
“…The participants had, during 90 days before the measurements, either consumed 150 ml of red wine/day for women or double the amount for men, or been in total alcohol abstention in a larger randomized study evaluating the nonacute effects of alcohol intake on cardiovascular risk factors. 22 This, however, turned out to have no significant effect on the microcirculatory results presented in this study. The measurements were done nonfasting during daytime after at least 12 h since alcohol intake in the wine consuming group.…”
Section: Subjects and Protocolcontrasting
confidence: 43%
See 1 more Smart Citation
“…The participants had, during 90 days before the measurements, either consumed 150 ml of red wine/day for women or double the amount for men, or been in total alcohol abstention in a larger randomized study evaluating the nonacute effects of alcohol intake on cardiovascular risk factors. 22 This, however, turned out to have no significant effect on the microcirculatory results presented in this study. The measurements were done nonfasting during daytime after at least 12 h since alcohol intake in the wine consuming group.…”
Section: Subjects and Protocolcontrasting
confidence: 43%
“…A borderline significant trend of increased liver fat and a decrease in LDL cholesterol was observed in wine consumers. 22 We found no significant statistical difference between the groups regarding the microcirculatory parameters. These results support the adequacy of pooling data from wine consumers and those that refrained from alcohol in this study.…”
Section: Discussionmentioning
confidence: 47%
“…Secondly, previous studies have shown an association between low-to-moderate alcohol consumption and lower risk for NAFLD, NASH and fibrosis [8,9,10]. Also, regular consumption of moderate amounts of alcohol, 150 ml of red wine per day for 90 days did not induce hepatic steatosis in healthy subjects [11]. However, population-based studies have indicated an interaction on the risk of liver damage between a high body mass index (BMI), which is highly associated with NAFLD [12], and alcohol consumption [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…Finally, beverages are so diverse that their LD should be considered individually: (1) wine is considered as a relevant source of betaine that could explain the French paradox (Mar and Zeisel, 1999). While moderate consumption has been associated with a reduced prevalence of suspected nonalcoholic fatty liver disease (Dunn et al, 2008), another study associated consumption with an increase in hepatic triglyceride accumulation, but not in steatosis (Kechagias et al, 2011), and thus wine consumption cannot yet be recommended to prevent steatosis; (2) sweetened beverages like soda should clearly be limited since they have been associated with a higher prevalence of steatosis (Abid et al, 2009;Zelber-Sagil et al, 2007); (3) coffee (LC = 537%, n = 7 LD) and tea (LC = 196%, n = 8 LD) are the beverages that appear to be the most significant and relevant sources of lipotropes; indeed, they have been associated in several studies with lowered hepatic fat accumulation and with general hepatic protection for high and/or regular drinkers (Freedman et al, 2009;Sakata et al, 2006;Gutierrez-Grobe et al, 2011;Iwai et al, 2002;Park and Bruno, 2010;Tillmann et al, 2011;Funatsu et al, 2011;Molloy et al, 2012).…”
Section: Discussionmentioning
confidence: 98%